Dampak integrasi pendekatan heutagogi dan e-learning dalam model flipped classroom terhadap kemampuan, strategi, dan motivasi membaca - Pramesti, Utami Dewi; Anshori, Dadang S.; Mulyati, Yeti; Sastromiharjo, Andoyo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to investigate the impact of the integration of the heutagogy (HA) and e-learning approaches in a flipped classroom on reading skills, strategies, and motivation. The method used in this study is quasi-experimental involving 351 high school students. Descriptive statistics and ANOVA were used in this study to test the effects of the intervention and compare them with other groups. The findings showed that the integration of the heutagogy and e-learning approaches in flipped classroom teaching was able to improve reading literacy skills, the use of reading strategies, and psychological factors that support the improvement of reading skills such as self-efficacy, reading motivation, and student autonomy. The principles of the heutagogy approach used in teaching reading skills are the the task, teacher support, student autonomy, evaluation. The most significant impact on reading skills and psychological factors of reading skill development is student autonomy. This study implies that the combination of the heutagogy (HA) and e-learning approaches can be an alternative for teachers to improve language skills, such as students' reading literacy skills.